REGULATION OF DRUGS IN MADHYA PRADESH: AN OVERVIEW : Pharmaceutical Sciences-Pharmaceutics - SURESH, KEMPAIAH; V, BALAMURALIDHARAN (International Journal of Life Science and Pharma Research, 2018)
Madhya Pradesh has been one of the pioneer States in India with an exemplary track record in the overall field of Pharmacy. The Drugs Control Administration in India exists at two tier system the Central and State Government level. The Central Drug Control Standard Organization (CDSCO) is works in making policy, if laws and rules at all India level. It controls the licensing such as approval of licence meant for manufacture of Large Volume Parenterals, Vaccine & Sera, Blood Bank and Blood Components, Medical devices and products manufactured by Recombinant technology and controls the new drug clearance, clinical trials, import registration, import of drugs etc., and inspections. Drugs Control Department in states deals with licensing of both manufacturing and sales establishments of Drugs & Cosmetics. Drugs Control Administration regulates the manufacture, sale and distribution of drugs to ensure their quality and efficacy. Madhya Pradesh is a pharmaceutical manufacturing hub fortified with sound knowledge based institutions and skilled human resource available in the state.It provides innovative, quality and affordable health care solution to the masses. In this short review author provides some of the glimpses of the Pharmacy and Regulation of Drugs in Madhya Pradesh.